2007
DOI: 10.1177/104063870701900405
|View full text |Cite
|
Sign up to set email alerts
|

Association of Myocarditis with High Viral Load of Porcine Circovirus Type 2 in Several Tissues in Cases of Fetal Death and High Mortality in Piglets. A Case Study

Abstract: Abstract. During a period of 1.5 months, a newly established pig herd experienced a high number of mummifications and stillbirths, a high neonatal mortality rate, and many piglets with congenital tremors or hind leg ataxia. After clinical and histological investigations, the submitted animals were divided into 4 groups: mummified or stillborn (N 5 6), live born with myocarditis (N 5 5) (average age 22.8 days), live born without myocarditis (N 5 14) (average age 20.0 days), and control animals from a different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 28 publications
3
45
1
7
Order By: Relevance
“…Similar pathomorphological changes as found in our study are described in several other works (Mikami et al 2005, Segales et al 2005, Martinez et al 2006, Brunborg et al 2007, Phaneuf 2007.…”
Section: Discussionsupporting
confidence: 80%
“…Similar pathomorphological changes as found in our study are described in several other works (Mikami et al 2005, Segales et al 2005, Martinez et al 2006, Brunborg et al 2007, Phaneuf 2007.…”
Section: Discussionsupporting
confidence: 80%
“…Presence and distribution of PCV2 antigen in various target tissues showing lesions characteristic of PMWS were similar to previous findings (Brunborg et al, 2007;O'Connor et al, 2001;Pallares et al, 2002;Rovira et al, 2002). Further, viral nucleic acid could be successfully demonstrated by ISH using DIG-labeled probe in lungs, heart, liver, lymph nodes and tonsil and these findings were similar to those reported earlier (Kim and Chae, 2001;Park et al, 2005).…”
Section: Discussionsupporting
confidence: 80%
“…The heart was not affected and was not further examined by either histology or IHC. In previous studies, the myocardium and the liver were shown to contain the highest amounts of PCV2, and the most consistent tissue lesions were found in the myocardium (West et al, 1999;Brunborg et al, 2007). The amount of PCV2 was reported to diminish with increased fetal age, and the virus is known to accumulate in the lymphoid organs around parturition (Sanchez et al, 2003).…”
Section: Discussionmentioning
confidence: 99%